Mickiewicz i inni Polacy we wspomnieniach rosyjskich memuarystek XIX wieku - Ambroziak, Daria (Acta Polono-Ruthenica, 2018)
The nineteenth century Russian women memoirism presents a valuable source of information concerning Polish-Russian literary relationships. A. Kern and A. Panaeva’s memoirs justify that A. Mickiewicz was a well-known and appreciated poet in Russia and his works were perceived by Russian literary elites as a symbol of struggle for national liberation. Russian publishers and editors of literary magazines played a crucial role in the popularization of Mickiewicz’s literary output. His poems, translated into Russian by Z. Sierakowski or W. Szczastny, often appeared in Russian literary magazines. Russian Decembrist writers (P. Annenkova and M. Volkonska) in their memoirs written in the Siberian exile presented in the most favourable light Poles (S. Leparski and M. Rukiewicz) who were also exiled to Siberia. But, on the other hand, in T. Bulharin’s memoirs, whose controversial activity was condemned by Russian intellectual elites, as well as in A. Smirnova’s opinion, which represented the official line of the Russian aristocracy, we find negative images of Poles and the “Polish question”.